2010
DOI: 10.1118/1.3481507
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of perfusion defect in five‐dimensional gated‐dynamic cardiac SPECT images

Abstract: Purpose: In previous work, the authors developed and demonstrated the concept of an image reconstruction procedure aimed to unify gated and dynamic nuclear cardiac imaging, which the authors have termed five-dimensional (5D) SPECT. Gated imaging permits the clinician to evaluate wall motion and, through the use of stress and rest scans, allows perfusion defects to be observed. Dynamic imaging depicts kinetics in the myocardium, which can be used to evaluate perfusion, but traditional dynamic images are motionl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…To obtain LVEF, a reconstructed 5D image sequence was first collapsed into a gated sequence by summing along the dynamic time axis; the clinical software package 4DMSPECT was then used to compute the EF from this collapsed sequence (Niu, Yang, Wernick & King 2010). …”
Section: Evaluation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain LVEF, a reconstructed 5D image sequence was first collapsed into a gated sequence by summing along the dynamic time axis; the clinical software package 4DMSPECT was then used to compute the EF from this collapsed sequence (Niu, Yang, Wernick & King 2010). …”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Despite these challenges, we recently demonstrated in (Niu, Yang, Wernick & King 2010) that 5D reconstruction could lead to useful dynamic information for discriminating between normal wall and perfusion defects in terms of their timevarying activities. The study in (Niu, Yang, Wernick & King 2010) made use of a 5D reconstruction approach previously developed in (Jin et al 2006, Niu, Yang, Jin, Wernick & King 2010), wherein the gated dynamic images were reconstructed jointly in order to exploit the correlation in the signal components among the different gate intervals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that despite the great challenges it is indeed feasible to obtain such a 5D image sequence, and that, more importantly, the kinetic information derived from the reconstructed dynamic images can be effective for discriminating normal from perfusion defects [5]. Built upon this prior success, in this work we explore an alternative, direct parametric reconstruction approach in This work was supported by NIH/NHLBI grant HL65425.…”
Section: Introductionmentioning
confidence: 95%
“…We used four non-overlapping and rotationally symmetric input channels (in spatial frequency domain) and modeled the internal observer noise [27,28]. A total of 200 noise realizations (100 for the uniform cylinder and 100 for the cylinder with spheres) were used for low- and high-noise simulated data reconstructed by TV-PAPA, FB-EM-TV, TVPF-EM and GPF-EM.…”
Section: Simulation Studiesmentioning
confidence: 99%